Impaired reduction of nocturnal systolic blood pressure and severity of diabetic retinopathy - Felício, João Soares; Pacheco, Juliana Torres; Ferreira, Sandra Roberta [UNESP]; Plavnik, Frida; Moisés, Valdir; Kohlmann Jr., Oswaldo; Ribeiro, Artur Beltrame; Zanella, Maria Tereza (My University, 2007)
The aim of the present study was to evaluate the influence of elevated levels of nocturnal blood pressure (BP) on diabetic retinopathy (DR). A total of 88 diabetic hypertensive patients were divided according to the stage of DR. They underwent 24 h ambulatory BP monitoring and ophthalmological evaluation, and their average level of fasting blood glucose as well as their glycemic control index (percentage of fasting blood glucose higher than 11.2 mmol/L over the previous four years) were calculated. When diabetic patients with retinopathy (n=29) (group 1) were compared with patients without retinopathy (n=59) (group 2), a significant difference was observed in diabetes duration (124 months [range six to 460 months] versus 43 months [range six to 365 months], respectively; P<0.05). In addition, group 1 showed higher levels of nocturnal systolic BP (NSBP) (141±22 mmHg versus 132±18 mmHg; P<0.05). However, no significant differences were found between the two groups (group 1 and group 2) when diurnal pressoric levels were compared (diurnal systolic BP, 153±19 mmHg versus 146±19 mmHg, P not significant; and diurnal diastolic BP, 91±9 mmHg versus 91±13 mmHg, P not significant). DR correlated with diabetes duration (r=0.26; P<0.05) and with glycemic control index (r=0.24; P<0.01). Multivariate regression analysis showed NSBP to be an independent predictor of DR (r2=0.12; P<0.01). Moreover, patients with severe stages of DR (preproliferative, proliferative or macular edema) showed a lower decrease of NSBP than the other patients (3.9±6.0 mmHg versus 9.2±6.0 mmHg; P<0.05). The present study suggests that the absence of 24 h normal pressoric rhythm can interfere with the prevalence and severity of DR. © 2007 Pulsus Group Inc. All rights reserved.
Keywords: Ambulatory blood pressure monitoring; Diabetic retinopathy; Hypertension; Type 2 diabetes mellitus